Strategi Kepemimpinan dalam Meningkatkan Kinerja Pegawai di Kementrian Agama Kabupaten Aceh Tengah - Muhtadi Muhtadi; Najmuddin Najmuddin; Syaiful Bahri (Journal on Education, 2025)
The objectives to be achieved from the implementation of this research activity are to analyze the performance of employees at the Ministry of Religious Affairs Office in the Ministry of Religious Affairs of Central Aceh Regency and to analyze the leadership strategy of the Head of the Ministry of Religious Affairs in improving employee performance at the Ministry of Religious Affairs Office in Central Aceh Regency. This study uses a Qualitative approach with a case study approach implemented at the Ministry of Religious Affairs Office in Central Aceh Regency. The subjects of this study were the Head of the Ministry of Religious Affairs Office in Central Aceh, Head of the TU Kemenag Sub-Division, Kasi and representatives of Employees/Staff. There are three data collection techniques used in this study, namely Observation, interviews, and documentation. Data analysis techniques through triangulation, namely data reduction, data presentation and data verification. The results of the study show: (1) Employee performance at the Ministry of Religious Affairs Office in Central Aceh based on the Employee Performance assessment which includes service orientation, integrity, commitment, discipline and cooperation is good, but there are still criteria among these elements that require special attention, namely employee commitment and discipline in working. (2) Leadership strategies to improve employee performance at the Aceh Tengah District Ministry of Religion Office are by establishing good communication and cooperation with employees, controlling employee performance, providing motivation and approaches to employees, conducting evaluations, providing training and development, and providing rewards and punishments to employees.